Fault–Based Liability for Medical Malpractice in the Age of Artificial Intelligence: Α Comparative Analysis of German and Greek Medical Liability Law in View of the Challenges Posed by AI Systems - Maroudas, Vasileios P. (Review of European and Comparative Law, 2024)
The rapid developments in the field of AI pose intractable problems for the law of civil liability. The main question that arises in this context is whether a fault-based liability regime can provide sufficient protection to victims of harm caused by the use of ΑΙ. This article addresses this question specifically in relation to medical malpractice liability. Its main purpose is to outline the problems that autonomous systems pose for medical liability law, but more importantly, to determine whether and to what extent a fault-based system of medical liability can adequately address them. In order to approach this issue, a comparative examination of German and Greek law will be undertaken. These two systems, while similar in substantive terms, differ significantly at the level of the burden of proof. In this sense, their comparison serves as a good example to “test” the adequacy of the fault principle in relation to AI systems in the field of medicine, but also to illustrate the practical importance that rules on the allocation of the burden of proof can have in cases of damage caused by the use of AI. As will eventually become apparent, the main problem appears to lie not in the fault principle itself, which, for the time being, at least in the form of objectified negligence, seems to protect the patient adequately, but mainly in the general rule for the allocation of the burden of proof, which is precisely why the fault principle ends up working to the detriment of the patient.